Fiabilité et fidélité : les logiques humaines et matérielles à l’œuvre dans les agences d’architecture de Pierre Dufau (1908-1985) - Hugo Massire (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Active from the late 1930s to the 1980s, Pierre Dufau (1908-1985) is one of the leading performers in the French architecture during the Trente Glorieusesperiod, due to the quantitative importance of his built production. Specialized in office buildings, public buildings and facilities, he was also involved in the field of urban planning by designing the reconstruction plan of the city of Amiens, and thirty years later by being responsible for the conception of the ‘Nouveau Créteil’masterplan, in Paris suburbs. This article proposes to study the structuring of the agency into a company offering products to its customers, and to draw a parallel with its historiographical construction, fed as much by journalistic criticism and historian expertise as by Pierre Dufau himself through the writing of his memoirs.